Evaluation of X-ray fluorescence for analysing critical elements in three electronic waste matrices: A comprehensive comparison of analytical techniques - Shaun T. Lancaster; Eskil Sahlin; Marcus Oelze; Markus Ostermann; Jochen Vogl; Valérie Laperche; Solène Touze; Jean-Philippe Ghestem; Claire Dalencourt; Régine Gendre; Jessica Stammeier; Ole Klein; et al. (Waste Management, 2024)

In‐use dissipation of technology‐critical elements from vehicles and renewable energy technologies in Vienna, Austria: A public health matter? - André Baumgart; Daniela Haluza; Thomas Prohaska; Simone Trimmel; Ulrike Pitha; Johanna Irrgeher; Dominik Wiedenhofer (Journal of Industrial Ecology, 2024)
The rollout of electric vehicles and photovoltaic panels is essential to mitigate climate change. However, they depend on technology‐critical elements (TCEs), which can be harmful to human health and whose use is rapidly expanding, while recycling is lacking. While mining has received substantial attention, in‐use dissipation in urban areas has so far not been assessed, for example, corrosion and abrasion of vehicle components and weather‐related effects affecting thin‐film photovoltaic panels. Therefore, the question arises to which extent TCEs dissipate during use and which potential non‐occupational human health impacts could occur. We assessed the available information on urban in‐use dissipation and human health concerns and conducted exploratory modeling of in‐use technology stocks, in‐ and outflows, and in‐use dissipation of neodymium, dysprosium, lanthanum, praseodymium, cerium, gallium, germanium, and tellurium contained in 21 vehicle and renewable energy technologies, for Vienna, Austria. In prospective scenarios, TCE dynamics in a trend‐continuation vis à vis official city policy plans and a more ambitious transition scenario were then assessed. We find that electrifying the vehicle fleet without demand‐reduction is the main driver of TCE consumption, effectively doubling cumulative end‐of‐life outflows to 3,073 [2,452–3,966] t and cumulative in‐use dissipation to 9.3 [5.2–15.7] t by the year 2060. Sufficiency‐based measures could reduce demand and in‐use dissipation well below levels with continued trends, thus highlighting the need to combine decarbonization with demand‐reducing measures. These results help assess potential future in‐use dissipation dynamics and inform discussions about potential public health hazards associated with exposure to TCEs accumulating in the urban environment.

Compost amendment in urban gardens: elemental and isotopic analysis of soils and vegetable tissues - Simone Trimmel; Stefan Wagner; Laura Feiner; Maria Feiner; Daniela Haluza; Rebecca Hood-Nowotny; Ulrike Pitha; Thomas Prohaska; Markus Puschenreiter; Philipp Spörl; Andrea Watzinger; Elisabeth Ziss; et al. (Environmental Science and Pollution Research, 2024)
Urban horticulture poses a sustainable form of food production, fosters community engagement and mitigates the impacts of climate change on cities. Yet, it can also be tied to health challenges related to soil contamination. This work builds on a previous study conducted on eleven urban gardens in the city of Vienna, Austria. Following the findings of elevated Pb levels in some soil and plant samples within that project, the present study investigates the elemental composition of soil and plants from two affected gardens 1 year after compost amendment. Inductively coupled plasma mass spectrometry (ICP-MS) analysis of skin, pulp and seeds of tomato fruits revealed minor variations in elemental composition which are unlikely to have an impact on food safety. In turn, a tendency of contaminant accumulation in root tips and leaves of radishes was found. Washing of lettuce led to a significant reduction in the contents of potentially toxic elements such as Be, Al, V, Ni, Ga and Tl, underscoring the significance of washing garden products before consumption. Furthermore, compost amendments led to promising results, with reduced Zn, Cd and Pb levels in radish bulbs. Pb isotope ratios in soil and spinach leaf samples taken in the previous study were assessed by multi-collector (MC-) ICP-MS to trace Pb uptake from soils into food. A direct linkage between the Pb isotopic signatures in soil and those in spinach leaves was observed, underscoring their effectiveness as tracers of Pb sources in the environment. Graphical Abstract

Green and blue infrastructure as model system for emissions of technology-critical elements - Simone Trimmel; Philipp Spörl; Daniela Haluza; Nagi Lashin; Thomas C. Meisel; Ulrike Pitha; Thomas Prohaska; Markus Puschenreiter; Elmar Rückert; Bernhard Spangl; Dominik Wiedenhofer; Johanna Irrgeher (Science of The Total Environment, 2024)